"Thrown away like a banana leaf": precarity of labour and precarity of place for Tamil migrant construction workers in Singapore. Issue 9 (2nd September 2019) - Hamid, Wajihah; Tutt, Dylan
Abstract: Despite labouring for three decades in Singapore, and being connected to the existing Tamil diasporic community there, Tamil migrant construction workers have been left out of state rhetoric and face economic marginalization and social exclusion. In this article, we draw on rich ethnographic data on their everyday experiences of working construction and living in Singapore, and we espouse the distinctive qualities and mission of ethnographically-informed methodologies to enact change in this space. The methods include in-depth interviews with 11 Tamil labourers, and the subsequent use of worker photo diaries, known as auto-photography, with a total of 108 photographs taken. All the participants either worked construction, were on medical leave, or were seeking compensation after workplace injury. The analysis of the interview data develops themes around precarity and discrimination on construction sites (precarity of work), and the exclusory social practices experienced by workers in their offsite world (precarity of place). Following the goals of decolonized research, our innovative methods have enabled Tamil construction workers to present their lives through their own lens. By involving migrant construction workers, we identify new sites of inquiry and knowledge in examining the inequalities and injustices they face.